The Analysis of Factors Associated with the Effectiveness of Nurse Communication to Patients in the Inpatient Room of Teungku Fakinah Hospital, Banda Aceh - Muhammad Iqbal Saputra; Said Usman; Sofia Sofia; Irwan Saputra; Yusni Yusni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aim of thisstudy is to find out the factors relating to the effectiveness of nurses communication in patient. The type of research in this study is quantitative analytic with cross sectional study approach. The research location is in the inpatient room of Teungku Fakinah Hospital in Banda Aceh. The result of the study are the effectiveness of nurse communication in patients at Teungku Fakinah Hospital is in the category of good at 89%, the value of the variables of openness, empathy, equality, audible (humble) and humble (humble) are in good category that is above 95%, factors that significantly affect the effectiveness of nurse communication in patients at Teungku Fakinah Hospital, namely the openness of empathy level, the level of equality of the audible level (right) and the level of humble (humble). The better the level of openness, the better the effectiveness of nurse communication in patients. The better the level of empathy, the better the communication effectiveness of nurses in patients. The better the level of equality, the better the effectiveness of nurse communication in patients.The better the level of audible (right), the better the effectiveness of nurse communication in patients.The better the level of humble (humble), the better the effectiveness of nurse communication in patients.